Afterpain: An Overview - Namboothiri, Smitha P. (Issues and Development in Health Research Vol. 2, 2021)
Women experience various kinds of physical discomforts after childbirth. Abdominal afterpain is one among them, which is an indicator of uterine involution (the process by which reproductive organs revert back into the pre-pregnant state). Afterpain usually goes undetected because of the predominating nature of other forms of pain and discomforts. This chapter is based on an original study aimed to identify the nature and characteristics of afterpain among postnatal mothers. This chapter seeks to identify the factors affecting the afterpain, experience of mothers on the abdominal afterpain and the key strategies in the management of afterpain.